Incidencia de las tic’s en la práctica profesional de las firmas auditoras en el cantón Quito, provincia de Pichincha en el año 2016 - Claudio Galarza, Miryam Rocío (2017)
The Information and Communication Technologies (ICTs) nowadays tools used on professional development for that reason is imperative to know their incidence in the audit area. The objective of this work has been the investigation of the management and knowledge of ICTs and the incidence of this in the professional practice of the audit firms of the Quito Canton, Pichincha Province. Starting from an investigation carried out to these firms, two fundamental arguments are concluded, the first that auditing firms have knowledge and use ICTs in general as: the internet, computers, smart phones, the office package and within these programs Which include Excel, Word, Power Point, etc. The second is that there is a need for auditing firms to be updated and trained in adequate and appropriate auditing programs….